Awareness of Child Sexual Abuse Among Secondary School Students in Kathmandu District - Basnet, Rojina; Gautam, Sabyata; Maharjan, Sharmila (Social Inquiry: Journal of Social Science Research, 2020)
This study explores the awareness among community and institutional school students on child sexual abuse (CSA). The study population was 120 students studying in class 8 and 9 from two institutional and two community schools. The numbers of male respondents were slightly higher than female respondents in both institutional and community schools (51.5% in institutional and 52.1% in community schools). 66% in community and 86.3% in community schools answered that raping the child and exposing abuser’s body parts to a child is sexual abuse of the child. Children perceive only serious forms or rape as sexual abuse while they are mostly ignorant that less serious types are also sexual abuse. However, comparatively respondents of community school were more aware of the non-contact form of sexual abuse of child than that of institutional school. Students of both institutional and community schools do not have much knowledge about the consequences of sexual abuse, as very few respondents hardly pointed out all the consequences. Furthermore, there was a difference in the level of knowledge between institutional and community school students. The result of the study will be useful to provide baseline information regarding awareness of school adolescents on sexual abuse so that policymakers can develop policies and programs to ensure a protective environment for children in various contexts. Also, awareness needs to be provided regarding CSA from primary school level.